2021
DOI: 10.1186/s13567-021-00951-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rapid and sensitive immunochromatographic strip based on EuNPs-ES fluorescent probe for the detection of early Trichinella spiralis-specific IgG antibody in pigs

Abstract: Trichinellosis, which is caused by nematodes of the genus Trichinella, is one of the most important zoonotic parasite diseases in the world. A rapid and sensitive immunochromatographic strip (ICS) based on Eu (III) nanoparticles (EuNPs) was developed for the detection of Trichinella spiralis (T. spiralis) infection in pigs. T. spiralis muscle larvae excretory secretory or preadult worm excretory secretory (ML-ES or PAW-ES) antigens were conjugated with EuNPs probes to capture T. spiralis-specific antibodies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…ICS outperforms ELISA in terms of detection speed and the reliability of results (base on the Cohen’s kappa coefficient). ICS also demonstrates significant advantages compared to ELISA in detecting Trichinella spiralis [ 26 ]. The results indicated that seroconversion of infection pigs was detected by ICS earlier than Qiagen ELISA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ICS outperforms ELISA in terms of detection speed and the reliability of results (base on the Cohen’s kappa coefficient). ICS also demonstrates significant advantages compared to ELISA in detecting Trichinella spiralis [ 26 ]. The results indicated that seroconversion of infection pigs was detected by ICS earlier than Qiagen ELISA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit anti-goat IgG antibodies (1 mg/mL) were coated on the NC membrane to make a C-line for quality control. After drying at RT for 3 h, the five parts were assembled in the direction of chromatography, cut into the width of 4 mm, and stored at 4 ℃ [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of the immunochromatographic assay techniques depended on the probes formed by antibodies and nanomaterials. The development of a fluorescence immunoassay has attracted extensive attention in recent years [ 40 , 41 ]. In this study, high-quality fluorescent probes were prepared using EuNPs and polyclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we developed an ECM-based ICS capable of detecting T. spiralis -specific IgG antibody in pig serums; the sensitivity, specificity, and cross-reaction were evaluated ( Wang et al., 2021 ). Aiming for clinical whole blood samples, we simplified the procedure and improved the effectiveness of the ECM-based ICS.…”
Section: Introductionmentioning
confidence: 99%